Cost-Effectiveness Analysis of Antithyroid Drug Therapy, 131I Therapy and Subtotal Thyroidectomy for Graves' Disease - YAMAMOTO, Masayoshi; KOSUDA, Shigeru; HAYASHI, Katsumi; WATANABE, Sadahiro; TANAKA, Yuji; KITA, Tamotsu; YANG, Fuzuki (RADIOISOTOPES, 2007)
The objective of this study was to assess the cost-effectiveness of antithyroid drug (ATD) therapy vs. radioiodine therapy (RIT) vs. subtotal thyroidectomy (STT) by calculating expected lifelong cost and utility based on Graves' disease patients' responses to questionnaires using a decision-tree sensitivity analysis and relevant variables. The decision-tree sensitivity analysis to determine expected lifelong cost and utility in Graves' disease patients was designed on the basis of the 4 competing strategies consisting of: (1) ATD therapy plus RIT strategy, (2) ATD therapy plus STT strategy, (3) low-fixed-dose (185 MBq) RIT alone strategy, and (4) high-fixed-dose (370 MBq) RIT alone strategy. One-way sensitivity analysis was designed in the ATD therapy plus RIT strategy, for replacement with RIT in place of ATD, ranging from a 100 incidence of ATD side effects to 30%. The low-fixed-dose RIT alone strategy was least costly, and the high-fixed-dose RIT alone strategy most costly. The lifelong utility of high-fixed-dose RIT alone strategy with a 5% rate of discounting was highest (lifelong utility for 30 years : 15.2/patient), and the utility of the ATD plus RIT strategy with 100 side effects of the ATD was lowest (14.1/patient) . The cost-effectiveness ratio was lowest (\5 008/utility) in a low-fixed-dose RIT alone strategy. In conclusion, a low-fixed-dose RIT alone strategy is preferred treatments in view of cost-effectiveness ratio, and RIT should be used more widely in Japan.